1997
DOI: 10.1002/(sici)1097-4547(19971115)50:4<549::aid-jnr6>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptors prevent nitric oxide-induced programmed cell death

Abstract: Activation of metabotropic glutamate receptor (mGluR) subtypes can prevent neuronal injury through the signal transduction pathways of nitric oxide (NO). It is this link to NO free radical injury and subsequent DNA damage that is the most intriguing. We therefore examined whether neuronal protection through mGluR activation was dependent on the molecular mechanisms of programmed cell death (PCD). The NO generators sodium nitroprusside and 3-morpholino-sydnonimine were administered to induce NO toxicity in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…1998), and β‐amyloid peptide (Copani et al. 1995) and nitric oxide‐induced programmed cell death (Vincent et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…1998), and β‐amyloid peptide (Copani et al. 1995) and nitric oxide‐induced programmed cell death (Vincent et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether the cytotoxicity of SNAP compared with that of SNP involved different mechanisms of cell death, we assessed DNA fragmentation as an indicator of apoptosis during the 18 h of incubation with SNAP or SNP. We performed a DNA laddering assay at 4, 6, 12, and 18 h, as it has been shown previously that apoptosis occurred after 6 h of incubation with SNP in hippocampal neurons (Vincent et al, 1997). With 0.5 m M SNP, no DNA ladder was seen after 4 h of incubation, but a laddering did appear after 6 h, increased after 12 h, and was still present after 18 h of incubation.…”
Section: Snap Induces Necrosis and Snp Induces Dna Fragmentationmentioning
confidence: 99%
“…However, the mechanisms of damage and protection are not well understood. Primary oligodendrocytes in culture are more susceptible to damage by NO than astrocytes and microglia (Mitrovic et al, 1994), although not as susceptible as some types of neurons (Vincent et al, 1997). Little information is available on the differential susceptibility of oligodendrocytes at various stages of differentiation.…”
mentioning
confidence: 99%
“…There is an equally abundant and credible body of evidence, though, that group I mGluR stimulation could be neuroprotective. Support for this viewpoint comes from studies of nitric oxide (NO)‐ or ischemia‐induced cell death,40,41 the associated reduction of apoptosis markers,42‐44 and NMDA toxicity 45,46. Bruno et al reported that the group I agonist DHPG was protective when coapplied with NMDA, despite an increase in NMDAR‐mediated currents 47.…”
Section: Neuroprotection By Glutamate Involves Group I Mglursmentioning
confidence: 99%